PEMANFAATAN LAYANAN DIFABEL DI PERPUSTAKAAN SASTRA MANGUTAMA DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN BADUNG - Berlian Ariezona, Shafara Hagelinia; Haryanti, Ni Putu Premierita; Widya Nugraha, A.A Bagus Surya (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2021)
ABSTRACT The pourpose this research aims to determine the use of disabled services in Mangutama Literature Library, Department of Archives, and Library of Badung District. This research was made qualitative research with the Haberman analysis technique. The data collection techniques used in this study were library observations, interviewing, taking photos for documentary evidence, and literature review. The informants in this study are the Service Sector and Preservation, librarians, and library users with disabilities. the utiliza-tion of disabled services has not been maximized because many facilities and accessibility are not yet available. Such as adding special accessibil-ity for the blindness that is special directions and a special floor (guiding block), adding the number of special computers, and adding a collection of special library materials for the disabled. The li-brary is also expected to add a collection of talking newspapers and e-books that are friendly for the disabled. Keywords: disabled, disabled services, disabled services at the library